2009
DOI: 10.1074/jbc.m806974200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell Motility by Spatial Repositioning of Enzymatic ATP/ADP Exchange Capacity

Abstract: ATP is the "principal energy currency" in metabolism and the most versatile small molecular regulator of cellular activities. Although already much is known about the role of ATP in fundamental processes of living systems, data about its compartmentalization are rather scarce, and we still have only very limited understanding of whether patterns in the distribution of intracellular ATP concentration ("ATP inhomogeneity") do exist and have a regulatory role. Here we report on the analysis of coupling of local A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 33 publications
1
60
0
1
Order By: Relevance
“…NAD dependent dehydrogenases play an important role in citric acid cycle, which is a main source of ATP production [23]. Adequate ATP supply is crucial for active restructuring of the actin cytoskeleton during the processes of cell movement and the change of cell shape [36]. Studies using fibroblast cells [36], heart endothelial cells [37], and erythrocytes [38] demonstrated that cytoskeletal dynamics were energy dependent; in other words, they relied on global ATP supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAD dependent dehydrogenases play an important role in citric acid cycle, which is a main source of ATP production [23]. Adequate ATP supply is crucial for active restructuring of the actin cytoskeleton during the processes of cell movement and the change of cell shape [36]. Studies using fibroblast cells [36], heart endothelial cells [37], and erythrocytes [38] demonstrated that cytoskeletal dynamics were energy dependent; in other words, they relied on global ATP supply.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate ATP supply is crucial for active restructuring of the actin cytoskeleton during the processes of cell movement and the change of cell shape [36]. Studies using fibroblast cells [36], heart endothelial cells [37], and erythrocytes [38] demonstrated that cytoskeletal dynamics were energy dependent; in other words, they relied on global ATP supply. In this study, Caco-2 cells dwelling inside wells formed more distinctive filopodia and spike-like protrusions than the cells growing on flat surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…It is however much weaker for mitotic cells, which have a much more compact morphology, and in which ATP diffusion from one place to another may not be a limiting factor. Yet, artificially targeting of ATPgenerating enzymes like the adenylate kinase close to specific ATP-demanding cytosolic locations appears to matter, even in compact dividing cells [46]. Thus steering mitochondria close to ATP demanding sites during mitosis (e.g.…”
Section: Mitochondria and Mitosis -Mechanism And Functionmentioning
confidence: 99%
“…In all organisms including pneumococci, intracellular ATP regulation is considered one of the most important factors for survival 15,16 . S. pneumoniae adenylate kinase (SpAdK) was crystalized and found to be essential for pneumococcal growth 3 .…”
Section: Introductionmentioning
confidence: 99%